When small is different: The case of membranes inside tubes - Perim, Eric; Fonseca, Alexandre F. [UNESP]; Galvão, Douglas S. (Springer Nature, 2013)
Recently, classical elasticity theory for thin sheets was used to demonstrate the existence of a universal structural behavior describing the confinement of sheets inside cylindrical tubes. However, this kind of formalism was derived to describe macroscopic systems. A natural question is whether this behavior still holds at nanoscale. In this work, we have investigated through molecular dynamics simulations the structural behavior of graphene and boron nitride single layers confined into nanotubes. Our results show that the class of universality observed at macroscale is no longer observed at nanoscale. The origin of this discrepancy is addressed in terms of the relative importance of forces and energies at macro and nano scales. © 2012 Materials Research Society.
Keywords: Cylindrical tubes; Elasticity theory; Macro scale; Macroscopic systems; Molecular dynamics simulations; Nano scale; Single layer; Structural behaviors; Thin sheet; Elasticity; Graphene; Molecular dynamics; Nanotechnology; Nanotubes; Tubes (components)